The Role of Community Participation Mediation in The Sustainability of Village Infrastructure - Muhammad Alfian Febrilian El-Fauzi; Mohammad Arif Rohman (Jurnal Ilmiah Dinamika Rekayasa, 2026)
Community participation has been proven to be an important factor in efforts to achieve infrastructure sustainability at the village level, with active community involvement in every phase of the construction project cycle. This research aims to identify the role of community participation in explaining the influence of planning & design and construction implementation on infrastructure sustainability in independent villages in Banyumas. This research uses quantitative methods. The stages of this research start with the collection of primary and secondary data, using questionnaires as a data collection tool. A total of 170 respondents were obtained from the distribution of questionnaires. The data were analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM) method. The results of this research indicate an indirect relationship (indirect effect) on community participation in mediating the impact of planning & design on infrastructure sustainability, which obtained a value of 0.391. The indirect relationship (indirect effect) on community participation in mediating the impact of construction implementation on infrastructure sustainability obtained a value of 0.272. These results are an indication that what needs to be considered is not only good planning and design and construction implementation, but also the involvement and active role of the community in each stage of the development process, in realizing optimal infrastructure sustainability in the village.